Case report: Periorbital pilomatricoma: a rare benign skin tumor misdiagnosed as cellulitis - Rahul Kumar; Jane Z. Spadaro; Jane Z. Spadaro; Alon Kahana; Alon Kahana; Alon Kahana (Frontiers in Ophthalmology)
PurposeWe describe an unusual case of a rapidly progressive pilomatricoma along the left brow, which was initially misdiagnosed and treated as preseptal cellulitis. Although rare, pilomatricomas and other adnexal tumors should be considered in the differential diagnosis of a growing mass near the brow.Case presentationA 29-year-old male presented to the emergency department with a progressively enlarging left brow lesion, initially noted 3 weeks prior. Exam revealed an erythematous left subbrow mass that measured 2.5 x 2 cm, with resultant mechanical ptosis. The lesion was initially misdiagnosed and treated as preseptal cellulitis, with concern for abscess. The patient ultimately underwent excisional biopsy of the lesion and pathology revealed pilomatricoma.ConclusionsPilomatricoma has similarities to more common skin lesions. Lack of pain or tenderness are important clues against an infectious or inflammatory etiology. Complete surgical excision is therapeutic and allows for diagnostic confirmation. Histopathology is required to rule out pilomatrix carcinoma, a malignant variant.